The Impact of Macro-Microeconomic Factors on Stock Price of Islamic Bank Listed on IDX - Muttaqi, Muhammad Ihsan; Surur, Miftakhus (SMART Insight, 2023)
Investors, however, also need to take into account the local economic trends. This has become a requirement for all Muslims worldwide and is done in order for the invested assets to become more productive and deliver the most benefit. This study intends to determine how macroeconomic and microeconomic variables (ROA, ROE, inflation, and GDP) affect the stock prices of Islamic bank listed on the IDX over a time period spanning 2016 to 2020 using the VAR/VECM method. The result show that there is no short-run correlation between any of the micro and macro variables, according to the results of the Vector Error Correction Model (VECM) test. On the other hand, there is a long-run correlation between the stock prices of Islamic Banks listed on the IDX and micro factors (ROA and ROE). In contrast to the ROA variable, Return on Equity (ROE) actually has a long-term negative impact on stock prices. Return on Assets (ROA) has a positive long-term impact on company prices. The ROE variable, regardless of the influence, whether it be positive or negative, makes the biggest percentage contribution to stock prices, followed by ROA, IPI, and then CPI.